Potensi Ekstrak Gulma Daun Sembung Rambat (Mikania micrantha H.B.K) Sebagai Bioherbisida Pengendali Gulma Putri Malu (Mimosa Pudica L.) - Mukarlina, Adin, Elvi Rusmiyanto Pancaning Wardoyo, (Jurnal Protobiont, 2017)
Sensitive plant (Mimosa pudica) is one of weeds that may cause harm to cultivated plants, both in terms of quantity and quality of production. Climbing hempweed (Mikania micrantha) has alelokimia compounds in form of phenol, terpenoids and flavonoids that can be used as bioherbisida. This study was aimed to determine the concentration of Climbing hempweed leaf (M. micrantha) extract to inhibit the germination and growth of Sensitive Plant (M. pudica). This research was conducted in February to April 2016 in Biology Department Screenhouse, Faculty of Science and Mathematics and Wood Technology Laboratory, Faculty of Forestry, Tanjungpura University, Pontianak. The study used completely randomized design which was consisted of 5 treatments and 5 replicates, the total were 25 units of trial. The climbing weed extract used as control were 0.1; 0.3; 0.5 and 0.7 g/ ml. The results showed that the extract withÂ  a concentration of 0.5 g / ml could inhibit the germination percentage and length of sensitive plant (M. pudica). M. micrantha leaf extract at a concentration of 0.3 g / ml could inhibit the growth such as the height, root length, wet weight, and dry weight of sensitive plant.